Wood pastures in Central Slovakia – collapse of a traditional land use form - Michal Wiezik; Tomáš Lepeška; Igor Gallay; Juraj Modranský; Branislav Olah; Adela Wieziková (Acta Scientiarum Polonorum. Formatio Circumiectus)
Wood pastures with pollard trees have been a common land-use type across Europe. The trees, besides having positive environmental effects on livestock, served as important source of fodder and wood. Pollarded wood pastures were hence a multifunctional, state of the art, highly productive farming ecosystems. Despite relatively drastic treatment, the trees regenerated quite well, and grew to relatively high-age. When pollarding lapses for longer period the wood pasture may confusingly resemble an ancient forest. Using aerial photographs of Slovakia from 1949–1950 we have identified 950 individual wood pasture localities with total area of 265.5 km2 within the Self-Governing Region of Banská Bystrica. Majority of identified wood pasture habitats were actively managed in the first half of the 20th century. Nowadays, less than 2.5% has preserved its original structure, the rest has been abandoned (92.8%) or actively transformed into different land-use form. We conducted a field survey in order to identify historical pollarding within the Gavurky protected area, one of the last and best preserved wood pastures in Slovakia. By evaluating habitual features, we were able to confirm historical pollarding for more than 80% of present veteran trees. We provide framework for identification of pollarding in historical wood pasture localities, applicable in the conditions of long-term management cessation.